(untitled) (International Seven Journal of Multidisciplinary, 2025)
Objective: To analyze the incidence of arrhythmias in dogs anesthetized with xylazine and induced with propofol, highlighting the clinical repercussions of this association, as well as the underlying physiological mechanisms and monitoring strategies. Veterinary anesthesia is essential for performing surgical and diagnostic procedures, but the combination of agents such as xylazine, an α2-adrenergic agonist, and propofol, an intravenous hypnotic, can significantly impact cardiovascular function. Xylazine causes sedation and pain relief, but may also lead to bradycardia and atrioventricular blocks. On the other hand, propofol causes myocardial depression and reduced blood pressure. The interaction between these drugs increases the probability of arrhythmias, making constant supervision through electrocardiogram (ECG) and other hemodynamic indicators essential. The implementation of individualized anesthetic protocols, combined with rapid strategies to correct cardiac alterations, is crucial to minimize risks. The review highlights the need for further studies on safe alternatives to anesthesia in dogs, seeking to reduce cardiovascular adverse effects.